Strategi Bisnis Internet Zappos.Com - Sartika Kurniali (ComTech: Computer, Mathematics and Engineering Applications, 2013)
Zappos established in 1999 runs its business by selling shoes online (e-commerce). The founder of the company originally wanted to provide the most diverse selection to its customers by providing all the brands, styles, sizes, and colors. Now Zappos begins to expand its product line. Zappos organizes all aspects of its business (including the hiring, organization's culture, call center, inventory, website, and supply chain) to provide the best service that gives a "wow" to each party that interacts with the company. Zappos grows rapidly. In 2008 its net sales (net of customer returns) of approximately $650 million. Even so, Zappos also faces a difficult time during recession. This case describes how the core competencies of a company's e-commerce which experiences early success quickly can survive a hit. Continuing to rely on organizational culture and customer service which are a long-term investment and relatively more expensive than other conventional approaches, Zappos can cut costs.